,,Vollgeld-Initiative“ gefährdet Geldwertstabilität - Alexander Rathke; Jan-Egbert Sturm; Klaus Abberger (Wirtschaftsdienst, 2018)
Am 10. Juni 2018 stimmen die Schweizer über die Volksinitiative 'Für krisensicheres Geld: Geldschöpfung allein durch die Nationalbank!' (Vollgeld-Initiative) ab. Die Initiative fordert, dass den Geschäftsbanken die Schaffung von elektronischem Geld untersagt wird. Neues Geld soll als Transfers an Bund/Kantone oder Bürgerinnen und Bürger in Umlauf gebracht werden. Aus Sicht der Autoren lassen sich die Schwächen des gegenwärtigen Systems durch andere Instrumente zuverlässiger beheben als durch die vorgeschlagene Reform. – – On 10 June 2018, Switzerland will hold a referendum on a people's initiative called 'Crisis proof money: Exclusive right to money creation for the Swiss National Bank!' (i.e. the Sovereign Money Initiative). According to the Initiative, banks should not have the right to create book money (deposits on sight). New money will be put into circulation via transfers to the federal government, cantons or citizens. The authors argue that the proposed reform is not a suitable measure to remedy shortcomings of the current system. Other, more traditional instruments are better suited.
Keywords: E3; E4; E5; 330